2017
DOI: 10.1002/cncr.30976
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in sexual function after ovarian cancer: Effects of sexual therapy and rehabilitation after treatment for ovarian cancer

Abstract: BACKGROUND: Sexual dysfunction is a distressing long-term effect after gynecological cancer and affects the majority of survivors for years after the completion of therapy. Despite its prevalence, treatment-related sexual dysfunction is underrecognized and undertreated for survivors. Thus, the aim of this study was to develop and test a brief psychoeducational intervention for managing sexual dysfunction for women who have undergone treatment for ovarian cancer (OC). METHODS: Forty-six OC survivors with docume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(80 citation statements)
references
References 52 publications
2
65
0
13
Order By: Relevance
“…Second, although the findings of the current study are promising, the lack of a control group limited our ability to conclude definitively that improvements in sexual function were not due merely to the passage of time. However, prior research has shown that time alone does not ameliorate sexual dysfunction . Nonetheless, randomized controlled trials are needed to demonstrate the efficacy of the multimodal intervention in enhancing sexual function, QOL, and mood in HCT survivors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, although the findings of the current study are promising, the lack of a control group limited our ability to conclude definitively that improvements in sexual function were not due merely to the passage of time. However, prior research has shown that time alone does not ameliorate sexual dysfunction . Nonetheless, randomized controlled trials are needed to demonstrate the efficacy of the multimodal intervention in enhancing sexual function, QOL, and mood in HCT survivors.…”
Section: Discussionmentioning
confidence: 99%
“…From September 20, 2015, to January 30, 2017, we screened 151 allogeneic HCT recipients and subsequently enrolled 47 of them at Massachusetts General Hospital (MGH) (http://ClinicalTrials.gov identifier NCT02492100). We chose to use a single‐arm pilot design because prior research has shown that sexual dysfunction does not resolve with the passage of time without intervention . A research assistant screened the weekly transplant clinic schedule to identify potentially eligible patients.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[52] Jinekolojik kanser sonrasında cinsel işlev bozuklukları ortaya çıkmakta, tedaviden yıllar sonra bile sağ kalanların çoğunu olumsuz olarak etkilemektedir. [53] Bu nedenle kişilerin cinsel işlev bozukluklarının erken evrede belirlenmesi ve müdahalelerinin yapılması önemlidir. Çinli kadınlar arasında jinekolojik kanser sonrasında yaşanan cinsel işlev bozukluğunun önemli bir endişe kaynağı olduğu ve bu kadınlarda %70,5 gibi yüksek bir oranda cinsel disfonksiyon görüldüğü belirtilmiştir.…”
Section: öZunclassified
“…Alguns estudos sugerem que mulheres com disfunções do assoalho pélvico como dispareunia, atrofia vaginal (VAZ et al, 2011b;ZHOU et al, 2016;HUFFM AN et al, 2016;SEKSE;HUFTHAMMER;VIKA, 2017) e insatisfação sexual (BRETSCHNEIDER et al, 2017), apresentaram redução da qualidade de vida. A abordagem das disfunções do assoalho pélvico nas sobreviventes ao câncer ginecológico é cada vez mais frequente, entretanto, não há um padrão de tratamento indicado (BOBER et al, 2018), sendo necessário conhecer o real impacto destas disfunções na função sexual para um melhor direcionamento das intervenções terapêuticas (WHICKER et al, 2017).…”
Section: Introductionunclassified